Antibiofilm activity and bioactive phenolic compounds of ethanol extract from the Hericium erinaceus basidiome - Sari Darmasiwi; Yaovapa Aramsirirujiwet; Ingorn Kimkong (Wolters Kluwer Medknow Publications, 2022)
Biofilm formation has become a serious health and environmental problem. Mushrooms are now considered a valuable source of bioactive compounds with antimicrobial properties. The lion's mane mushroom (Hericium erinaceus [HE]) has been used as an antimicrobial for ulcers and gastritis in East Asian countries. However, studies on the antibiofilm activities of HE basidiome against biofilm-forming pathogenic bacteria and their bioactive compound profiles are still limited. The purpose of this study was to determine the antibiofilm activity of HE and to identify its phenolic compound profile. The HE inhibitory activities against bacterial growth and biofilm formation were performed against Pseudomonas aeruginosa, Salmonella Typhimurium, Proteus mirabilis, and Staphylococcus aureus. Remarkably, P. mirabilis was the most susceptible bacteria to HE. The total phenolic content (TPC) of HE was 1652 ± 1.06 μg/ml, with protocatechuic acid and p-coumaric acid being the most abundant phenolic compounds as determined by high-performance liquid chromatography-mass spectrophotometry (HPLC-MS). This research highlights the possibility of HE as an antibiofilm agent that can be developed as a nutraceutical and natural food preservative.